P0658MATRIX AND FLOW MODULATE GENE EXPRESSION IN A 3D VASCULARISED TUBULE MODEL. (6th June 2020) - Williams, Julie; Robinson, Sanlin; Alaei, Babak; Homan, Kimberly; Clausen, Maryam; Hicks, Ryan; Belfield, Graham; William-Olsson, Lena; Bak, Annette; Lewis, Jennifer; Laerkegaard Hansen, Pernille
Abstract: Background and Aims: Questions abound regarding the translation of in vitro 2D cell culture systems to the human setting. This is especially true of the kidney in which there is a complex hierarchical structure and a multitude of cell types. While it is well accepted that extracellular matrix plays a large part in directing cellular physiology emerging research has highlighted the importance of shear stresses and flow rates too. To fully recapitulate the normal gene expression and function of a particular renal cell type how important is it to completely reconstitute their in vivo surroundings? Method: To answer this question, we have cultured proximal tubular (PT) epithelial cells in a 3-dimensional channel embedded within an engineered extracellular matrix (ECM) under physiological flow that is colocalised with an adjacent channel lined with renal microvascular endothelial cells that mimic a peritubular capillary. Modifications to the system were made to allow up to 12 chips to be run in parallel in an easily handleable form. After a period of maturation under continuous flow, both cell types were harvested for RNAseq analyses. RNA expression data was compared with cells cultured under static 2-dimensional conditions on plastic or the engineered ECM. Additionally, the perfusion of glucose through this 3D vascularised PT model has been investigated in the presence and absence of known diabetes modulating agents. Results: PCA of RNAseq data showed that a) static non-coated, b) static matrix-coated and c) flow matrix-coated conditions separated into 3 distinct groups, while cell co-culture had less impact. Analysis of transcriptomic signatures showed that many genes were modulated by the matrix with additional genes influenced under flow conditions. Several of these genes, classified as transporters, are of particular importance when using this model to assess drug uptake and safety implications. Co-culture regulated some interesting genes, but fewer than anticipated. Preliminary experiments are underway to monitor glucose uptake and transport between tubules under different conditions. Conclusion: We have developed a medium throughput system in which matrix and flow modulate gene expression. This system can be used to study the physiology of molecular cross-talk between cells. Ongoing analysis will further consider relevance to human physiology.